PIK-R Persuasive Communication in Preventing Early Marriage: Case Study in Sikunang Village - Yudha Pradhana; Ariandi Putra (Universitas Widya Mataram, 2024)
Early marriage, a phenomenon of marriage that occurs before the age of majority or before free and legal consent, is a social problem that has a wide impact in many countries, including Indonesia. This reality is further exacerbated by data obtained from UNICEF that as of the end of 2022, Indonesia is currently ranked 8th in the world and 2nd in ASEAN as a country with the number of early marriages or marriages of underage children, with a total of nearly 1.5 million cases. In an effort to overcome early marriage, persuasive communication through various media and platforms has been considered an effective tool for increasing awareness and changing people's attitudes and behavior. The PIK-R (Youth Information and Counseling Center) program has become a significant initiative in providing information and support to teenagers in facing social issues, including early marriage. This research will examine and analyze the persuasive communication carried out by PIK-R in preventing early marriage in Sikunang Village, Wonosobo, Central Java. The aim of this research is to understand and analyze the persuasive communication strategies carried out by PIK-R. Data was taken from observation transcripts as well as conducting direct interviews with members and people in charge of PIK-R Sikunang Village. The research approach used by researchers is a descriptive qualitative approach which aims to analyze how persuasive communication is carried out by PIK-R in preventing early marriage in Sikunang Village, Wonosobo, Central Java. The results of this research found that the persuasive communication carried out by PIK-R Sikunang Village in prevention was considered not yet optimal and needed to be improved further in its implementation Central Java. Keywords: Communication; Persuasive Communication; Early Marriage; Youth PIK